The Effect Of Profitability And Liquidity On Tax Aggressiveness With Good Corporate Governance As A Moderation Variable - Yhoga Heru Pratama; Antonius Rizky (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
The aim of this research is to explore how profitability and liquidity influence tax aggressiveness, by considering the role of good corporate governance as a moderating factor. This research uses a sample of manufacturing companies listed on the Indonesia Stock Exchange (BEI) during the 2019-2022 period. The research methodology used uses quantitative methods. The population in this study were 193 manufacturing companies registered on the IDX. The sample used was 316 samples from the results of 79 companies multiplied by four years of financial reports selected using the purposive sampling method. Next, the collected data was analyzed using the SPSS program for multiple linear regression. The significance level used to test the hypothesis is 5%. The research results show that liquidity and profitability have a positive impact on tax aggressiveness. In addition, it was revealed that good corporate governance weakens the influence of profitability on tax aggressiveness, although it does not succeed in moderating the influence of liquidity on tax aggressiveness.